A KDM4-DBC1-SIRT1 Axis Contributes to TGF-b Induced Mesenchymal Transition of Intestinal Epithelial Cells - Chen, Baoyu; Dong, Wenhui; Shao, Tinghui; Miao, Xiulian; Guo, Yan; Liu, Xingyu; Feng, Yifei (Frontiers in Cell and Developmental Biology, 2021)
Intestinal fibrosis is one of the common pathophysiological processes in inflammatory bowel diseases (IBDs). Previously it has been demonstrated that epithelial-mesenchymal transition (EMT) can contribute to the development of intestinal fibrosis. Here we report that conditional ablation of SIRT1, a class III lysine deacetylase, in intestinal epithelial cells exacerbated 2, 4, 6-trinitro-benzene sulfonic acid (TNBS) induced intestinal fibrosis in mice. SIRT1 activity, but not SIRT1 expression, was down-regulated during EMT likely due to up-regulation of its inhibitor deleted in breast cancer 1 (DBC1). TGF- augmented the recruitment of KDM4A, a histone H3K9 demethylase, to the DBC1 promoter in cultured intestinal epithelial cells (IEC-6) leading to DBC1 trans-activation. KDM4A depletion or inhibition abrogated DBC1 induction by TGF- and normalized SIRT1 activity. In addition, KDM4A deficiency also attenuated TGF- induced EMT in IEC-6 cells. In conclusion, our data identify a KDM4-DBC1-SIRT1 pathway that regulates EMT to contribute to intestinal fibrosis.